Penerapan Model Pembelajaran Quick on The Draw Untuk Meningkatkan Kemampuan Komunikasi Matematis mahasiswa - Nur Afifah (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. This study aims: (1) to determine the magnitude of the increase in students' mathematical communication skills with the Quick on The Draw learning model; (2) determine the level of activity of students and lecturers in learning through the Quick on The Draw learning template. This research was conducted with the method of classroom action research (Classroom Action Research) with two cycles. This research was conducted at the Mathematics Education Study Program, FKIP UMSU. The subjects are 4th semester students with a total of 30 students. The object of research is the ability of lecturers to manage learning and student activities in the implementation of learning and the ability of students to communicate mathematically through the Quick on The Draw learning model on the Diophantus equation material. The results of the research before the action showed the average percentage of mathematical communication skills was 48.87. The results of the first cycle of research showed that the average percentage of mathematical communication skills was 70.80, the average percentage of lecturers' activity observations was 77.62, and the average percentage of student activity observations was 78.08 with a classical completeness percentage of 33. The results of the cycle cycle II shows the average percentage of mathematical communication skills is 81.73, the average percentage of lecturer activity observations is 89.98, and the average percentage of student activity observations is 87.12 with a classical completeness percentage of 87. The conclusion of this study is Quick on The Draw can improve students' mathematical communication skills and Learning with Quick on The Draw learning can make students' activities categorized as good in learning. Suggestions that can be put forward are Quick on The Draw can be implemented by lecturers to improve students' mathematical communication skills.Abstrak. Penelitian ini bertujuan: (1) mengetahui besar peningkatan kemampuan kemampuan komunikasi matematis mahasiswa dengan model pembelajaran Quick on The Draw; (2) mengetahui kadar aktivitas mahasiswa dan dosen dalam pembelajaran melalui moldel pembelajaran Quick on The Draw. Penelitian ini dilakukan dengan metode penelitian tindakan kelas (Classroom Action Research) dengan dua siklus. Penelitian ini dilaksanakan di Prodi Pendidikan Matematika FKIP UMSU. Subjeknya adalah mahasiswa semester 4 dengan jumlah 30 mahasiswa. Objek penelitian adalah kemampuan dosen mengelola pembelajaran dan aktivitas mahasiswa dalam pelaksanaan pembelajaran serta kemampuan mahasiswa dalam komunikasi matematis melalaui model pembelajaran Quick on The Draw pada materi persamaan Diophantus. Hasil penelitian sebelum tindakan menunjukkan persentase rata-rata kemampuan komunikasi matematis sebesar 48,87. Hasil penelitian siklus I menunjukkan persentase rata-rata kemampuan komunikasi matematis sebesar 70,80, persentase rata-rata hasil observasi aktivitas dosen 77,62, dan persentase rata-rata hasil observasi aktivitas siswa 78,08 dengan persentase ketuntasan klasikal 33. Hasil penelitian siklus II menunjukkan persentase rata-rata kemampuan komunikasi matematis sebesar 81,73, persentase rata-rata hasil observasi aktivitas dosen 89,98, dan persentase rata-rata hasil observasi aktivitas mahasiswa 87,12 dengan persentase ketuntasan klasikal 87. Kesimpulan dari penelitian ini adalah Quick on The Draw dapat meningkatkan kemampuan komunikasi matematis siswa dan Pembelajaran dengan pembelajaran Quick on The Draw dapat membuat aktivitas siswa berkategori baik dalam pembelajaran. Saran yang dapat diajukan adalah Quick on The Draw dapat dilaksanakan oleh dosen untuk meningkatkan kemampuan komunikasi matematis mahasiswa.